Disseminating Your Study Results to Maximise Implementation in Practice: A Practical Framework for Intensive Care Nursing. - Tume, Lyvonne N. (Nursing in Critical Care, 2026)
The article focuses on the IMPACTS framework, a practical strategy designed to enhance the translation of research evidence into intensive care unit (ICU) nursing practice. IMPACTS stands for Identifying stakeholders, Motivating engagement, Planning dissemination, Administering strategies, Contributing meaningful communication, Developing clinical tools, and Seeking evaluation of uptake. The framework emphasizes tailoring communication to diverse stakeholders—including bedside staff, managers, patients, and policymakers—and using varied formats such as infographics, clinical algorithms, and presentations to facilitate implementation. It also highlights the importance of proactive, multi-level dissemination and ongoing assessment of practice change, addressing the common delay in integrating research findings into ICU care.